Taking "some" of the mimicry out of the adoption process: Quality management and strategic substitution - Joseph A. Clougherty; Michał Grajek; Oz Shy (European School of Management and Technology (ESMT), 2016)
Operations management scholarship has focused on reference-group adoption positively influencing focal-facility adoption; i.e., positive imitation parameters manifest due to the presence of mimicry and contagion. We instead argue that the incentive to adopt a quality-management system can be inversely related to reference-group diffusion. Our theoretical model formalizes the potential for strategic substitution and negative imitation parameters to be applicable in quality-management adoption. We compile a dataset of 2,895 facility-level observations that allows for three different industry-level reference groups; i.e., domestic industry, domestic exporters and foreign exporters. When undertaking probit estimations that do not account for appropriate fixed effects, we find positive imitation parameters which support the presence of mimicry and contagion. Yet when accounting for fixed effects, the imitation parameters turn negative in line with the presence of strategic substitution. Furthermore, the negative influence of reference-group adoption on focal-facility adoption is robust across the three reference groups.
Keywords: 650; adoption; quality management; standards; mimicry; contagion